Beyond the guidelines: outcomes of extremely delayed hip fracture surgery in elderly - Tugcan Demir; Kaan Suleyman Irgit; Emre Seyhan; Oguzhan Cimen; Halil Karaca (BMC Musculoskeletal Disorders)
Abstract Background Hip fractures are a significant public health issue among the elderly. While early surgical intervention’s effects on morbidity are well-documented, the impact of delayed surgery on mortality and morbidity is less understood. This study aims to examine the medium-term morbidity and mortality in patients who underwent delayed surgery with an average preoperative waiting period of 14 days. Materials This retrospective study used data from hospital records, Social Security Institution death records, and telephone surveys. Included were patients aged 65 and older with femoral neck or pertrochanteric fractures. Excluded were those younger than 65, with pathological or subtrochanteric fractures, and without adequate preoperative and postoperative follow-up. Preoperative waiting time, mobilization status, ASA score, NLR, and mortality rates were recorded. Postoperative follow-ups occurred at 2, 6, and 12 weeks, 6 months, 1 year, and annually. Various statistical methods investigated the impact of preoperative waiting time on mortality and mobility. Results A total of 289 hip fracture surgeries were followed for an average of 5.1 years (range: 0-8.5 years). The mean age was 79 (range: 65–100), with 174 females (60.2%) and 115 males (39.8%). The average preoperative waiting time was 14 days (range: 0–49 days). ROC analysis indicated the critical mortality threshold was 12 days. The one-month cumulative mortality rate was 6% for patients operated on within the first 12 days and 11% for those operated on after 12 days. One-year cumulative mortality rates were 21% for patients operated on within 12 days and 39% for those operated on after 12 days. Conclusion This study confirms the relationship between surgical delay and increased mortality rates in hip fracture patients, with a 12-day threshold for high mortality risk exceeding typical reports. While no statistically significant relationship was found between preoperative waiting time and ambulation, one-third of postoperative patients could walk without support and nearly half could not walk at all. Despite being retrospective, this study with a large patient population demonstrates the significant impact of surgical delay on mortality and morbidity rates in hip fracture patients.